Ảnh hưởng của thời gian và nhiệt độ đến hiệu quả ức chế ăn mòn thép cacbon bởi natri silicat và natriphotphat trong nước đã khử khí oxi - Huy và cộng sự, Vũ Đình (Vietnam Journal of Chemistry, 2014)
Effects of sodium silicate and sodium orthophosphate on the carbon steel corrosion inhibition in deoxygenated water at temperatures from 30oC to 140oC has studied by mass loss, potentiodynamic polarization and electrochemical impedance spectroscopy methods. Sodium silicate and sodium orthophosphate concentrations were surveyed from 0 to 500 ppm. The experimental results showed that: 1. The carbon steel corrosion inhibition efficiency of sodium silicate and sodium orthophosphate depend on temperature. The best result was obtained at 60oC; 2. The optional synergistic combination for controlling carbon steel corrosion in deoxygenated water is sodium silicate (500 ppm) and sodium orthophosphate (100 ppm); 3. Sodium silicate is an anodic inhibitor, and sodium orthophosphate acts as a cathode inhibitor.